Determinación del nivel de eutrofización del Embalse Sixto Duran Ballén mediante índices de estado trófico. - Moreira Santos, Joselyn Yeritza (2016)
The present research is focused on knowing the trophic condition in Sixto Duran Ballen reservoir of Bolivar Canton; the study was not experimental, monthly samplings were made to measure parameters insitu and laboratory both physicists and chemists; applying Carlson's IET methodology for the analysis of moderated waters which was adapted by Toledo for tropical waters. PH measurements were made with an average of monthly measurements of 9,5; Temperature of 29ºC, CE 202 µS/cm, OD of 6,5 Mg/l, Depth of 0,5 m, PT of 635 u/l and Chlorophyll to 41,7u/l in 5 points; 3 correspond to the river mouths representative by the rivers of Rio Grande, Rio Barro, Rio Caña Grande, and 2 points inside the reservoir. The samplings were done during October, November and December, 2015. With the information obtained Depth, Phosphorus and Chlorophyll were calculated the IET using the modified methodology of Toledo (1982), obtaining general average of the IET of 82 which indicates that the reservoir presents an eutrophic condition because the classification of Toledo. If this value is superior to 55 the aquatic species present in the reservoir will be affected by the excess of nutrients and consequently the proliferation of anoxic algae that makes the oxygen exhausted because of the breathing and decomposition of them, provoking the death by asphyxiation of the organisms.